2014
DOI: 10.4025/actascianimsci.v36i4.24446
|View full text |Cite
|
Sign up to set email alerts
|

<b>The impact of dietary dry yeast on lactation curves of primiparous and multiparous Saanen goats

Abstract: Twenty-four Saanen goats (fifteen multiparous and nine primiparous) during their lactation period were used, from the kidding until the 200 th day of lactation; and were distributed in a completely randomized design and in a factorial arrangement (3 diets x 2 parity orders). The diets were composed of either soybean meal (SBM), soybean meal plus inactive dry yeast (SMDY) or inactive dry yeast (DY) used as the protein source. The analyses of milk yield, body weight and dry matter intake (DMI) were made through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
(3 reference statements)
0
5
1
Order By: Relevance
“…It is noteworthy that the nutritional requirements in this study were according to AFRC (1993) for Saanen goats with body weights of 60 kg and a milk yield of 3.0 kg per day, and that the data obtained in this study was thus similar to that predicted by this nutrition council. The milk yield at the beginning of lactation (2.16 kg/day) and at the peak (3.86 kg/day) was lower than reports of other studies for Saanen goats under tropical climate conditions, as mentioned by Gomes et al (2014) and Souza et al (2014), and close to that reported by Macedo et al (2001) and Zambom et al (2005). These differences must be due to the variations in the ingredients and compositions of diets.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…It is noteworthy that the nutritional requirements in this study were according to AFRC (1993) for Saanen goats with body weights of 60 kg and a milk yield of 3.0 kg per day, and that the data obtained in this study was thus similar to that predicted by this nutrition council. The milk yield at the beginning of lactation (2.16 kg/day) and at the peak (3.86 kg/day) was lower than reports of other studies for Saanen goats under tropical climate conditions, as mentioned by Gomes et al (2014) and Souza et al (2014), and close to that reported by Macedo et al (2001) and Zambom et al (2005). These differences must be due to the variations in the ingredients and compositions of diets.…”
Section: Discussioncontrasting
confidence: 51%
“…By evaluating the lactation curves of Saanen goats through Wood's nonlinear model, Takma et al (2009) showed that the increased rate of yield until lactation peak was 0.13 and Gomes et al (2014) showed a range from 0.03 to 0.13. Nevertheless, in this research, the rate of yield increased from 0.18 to 0.24, which agrees with Zambom et al (2005), who found values ranging from 0.10 to 0.27, and Tufarelli et al (2009), whose values ranged from 0.21 to 0.29 for the increased rate of yield until lactation peak.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, in the last three weeks before calving a compression of the rumen by the fetus occurs and dry matter intake can be reduced by about 5 to 10% (RIBEIRO, 1997). Also, in early lactation, intake capacity is still critical, until the 7 th to 11 th week, when dry matter intake is completely restored (GOMES et al, 2014b).…”
Section: Resultsmentioning
confidence: 99%
“…The Bayesian analysis is an approach that works on datasets with true distribution, being reliable for small groups of data (Alves et al 2011). It has been used to obtain precise estimates without needing any kind of transformation (Gomes et al 2014). The statistical method revealed the absence of a statistically significant difference between the germination speed of controls and treatments.…”
Section: Contentsmentioning
confidence: 99%